Power system development and carbon dioxide emission reduction in China - Ji, L (Oxford Institute for Energy Studies, 2014)
With China’s rapid economic development, energy and electricity consumption are growing very fast. From 2001 to 2012, the annual average growth rate of energy consumption and electricity consumption were 7.9 per cent and 11.5 per cent respectively. This in turn led to a significant increase in China’s CO2 emissions. In 2000, China’s CO2 emissions were about half the US level and per capita CO2 emissions were two-thirds the average global level. However, in 2008, China became the world’s largest emitter of CO2. In 2010, China’s CO2 emissions from energy combustion were 7.12 billion tonnes, accounting for over a fifth of global CO2 emissions, and per capita emissions surpassed the world average level. Between 2000 and 2010, China contributed 60 per cent of the increase in global CO2 emissions.